Peddling Pedagogies: The Winners and Losers of a Standardized Testing Economy - Steele, Lucy Arnold (Radical Teacher, 2014)
This review compares the ethnographic research of Jessica Zacher Pandya’s Overtested: How High-Stakes Accountability Fails English Language Learners with the programmatic prescriptions of Yvette Jackson’s Pedagogy of Confidence. Both texts are concerned with the impact of standardized testing on urban students, but the focus of each book is quite different in terms of public policy on education and the way teacher roles are construed.